Tibetan medicine Jiuwei Qingpeng San could inhibit influenza A virus induced lung injury via regulating the expression of IFN-γ and its signaling pathway - Liu Wei; Li Chufang; Song Jian; Li Jintao; Liang Liren; Cai Kaiyin; Wang Yinong; Chen Weiwu; Chen Lvyi; Hou Hongping; Mingji Cuomu; Zhong Nanshan (Elsevier, 2023)
Introduction: The Tibetan formula Jiuwei Qingpeng San (JWQPS) has been applied for severe respiratory infection with a centuries-old history and contemporarily applied for influenza induced pneumonia. Although it is empirically effective, its antiviral efficacy and the underlying mechanisms against influenza A (IAV) virus induced lung injury have not been elucidated yet. Methods: The in vitro anti-viral activity of JWQPS against H1N1 was reflected by the detection of cell viability of PR8 infected BEAS-2B cells. A replication competent PR8 carrying Gaussia luciferase (PR8-Luci) was further utilized to infect BEAS-2B cells to determine the inhibitory activity of virus replication by detection of the intensity of bioluminescence that correlates with viral load. Transcriptome was utilized to analyze the differences of the gene expression profiles in BEAS-2B cell line between the groups with or without JWQPS treatment after PR8 infection. BALB/c mice were intranasally inoculated with 60 or 150 p.f.u. of PR8 and intragastric administered with JWQPS (400 mg/kg/day, 200 mg/kg/day, 100 mg/kg/day). The mice infected with lethal dosages of 60 p.f.u. were monitored and weighed daily for 14 days and the survival rates were calculated. Concentrations of Nucleoprotein (NP) of IAV in BALF that stand for viral load were determined at 3 or 6 d.p.i. by enzyme linked immunosorbent assay (ELISA). Interferons and lymphotactin in the BALF collected at 3 d.p.i. were detected with the corresponding ELISA kits. The level of pro-inflammatory cytokines in BALF collected at 6 d.p.i. were detected using Th1/Th2 Cytokine 11-Plex Mouse ProcartaPlex Panel. The numbers of leukocyte in BALF were counted by an automated blood cell counter. The lung tissues of mice that were not subjected to BALF collection were harvested at 6 d.p.i. to check lung lesions by hematoxylin-eosin staining and lung coefficient calculation. Results: JWQPS inhibited IAV replication in vitro, down regulated NP in BALF of H1N1 infected BALB/c mice and protected the mice from IAV caused death. The elevated level of lymphotactin, IFN-γ and lymphocytes in BALF were observed 3 days post infection after JWQPS administration. The improved lung lesions, the alleviated leukocytes infiltration, and the decreased pro-inflammatory levels were observed 6 days post infection. Transcriptomic analysis of H1N1 infected lung epithelial cell line revealed JWQPS treatment could dramatically regulate the genes involved in defense response to virus and interferon associated signaling pathways. Discussion: Our study indicated that JWQPS could promote the chemotactic effect of lymphocytes towards site of infection to eliminate the pathogen at early phase of infection and alleviate the development of inflammation thereafter by reducing the occurrence of neutrophils and lymphocytes into the pulmonary alveoli by a rather complicated regulatory network in immune responses.